Establishing an Integrative Medicine Program Within an Academic Health Center: Essential Considerations. (September 2016) - Eisenberg, David M.; Kaptchuk, Ted J.; Post, Diana E.; Hrbek, Andrea L.; O'Connor, Bonnie B.; Osypiuk, Kamila; Wayne, Peter M.; Buring, Julie E.; Levy, Donald B.
Abstract : Integrative medicine (IM) refers to the combination of conventional and "complementary" medical services (e.g., chiropractic, acupuncture, massage, mindfulness training). More than half of all medical schools in the United States and Canada have programs in IM, and more than 30 academic health centers currently deliver multidisciplinary IM care. What remains unclear, however, is the ideal delivery model (or models) whereby individuals can responsibly access IM care safely, effectively, and reproducibly in a coordinated and cost-effective way. Current models of IM across existing clinical centers vary tremendously in their organizational settings, principal clinical focus, and services provided; practitioner team composition and training; incorporation of research activities and educational programs; and administrative organization (e.g., reporting structure, use of medical records, scope of clinical practice) and financial strategies (i.e., specific business plans and models for sustainability). In this article, the authors address these important strategic issues by sharing lessons learned from the design and implementation of an IM facility within an academic teaching hospital, the Brigham and Women's Hospital at Harvard Medical School; and review alternative options based on information about IM centers across the United States. The authors conclude that there is currently no consensus as to how integrative care models should be optimally organized, implemented, replicated, assessed, and funded. The time may be right for prospective research in "best practices" across emerging models of IM care nationally in an effort to standardize, refine, and replicate them in preparation for rigorous cost-effectiveness evaluations.